A study on the discretionary acts of local government and local government heads: focusing on accounting irregularity. (2nd January 2023) - Hong, Yoonpyo; Jeong, Jisu
ABSTRACT: This study examines the relationship between allowances for bad debts in connection with tax and budget accounting irregularity. In particular, we tried to verify the relationship between the provision of distorted financial accounting information and the occurrence of budget accounting misconduct in pursuit of political benefits by theoretical discussion and empirical analysis. We collected the panel datasets for the period 2008 to 2012 from local governments in South Korea. The logistic regression confirmed the tendency in local governments of avoiding the detection of budget-related irregularity through the act of setting the allowance ratio for bad debts for tax. This can be highlighted as a problem, in that there is a discretionary portion in setting the ratio of the allowance for bad debts for tax and a lack of control of the distortion between the information on the budget accounting irregularity and the information in the financial accounting settlement.